(untitled) (Materiali di Estetica. Terza serie, 2025)
Through the experience of drawing from life, it is possible to train knowledge through conscious and unconscious mirroring in the self. It is possible to understand knowledge as readiness for the most generative emptiness, bringing oneself into the absence of narrow conditioning and welcoming creative reactions from multiple natures of multiplied stimuli. Provoking emptiness and silence to artistically contaminate sensations and artistic expression.